Edukasi Karakteristik Genetik dan Diagnostik Molekuler Virus Dengue Serta Upaya Pencegahan Infeksinya melalui Lilin Aromaterapi - Fitria Diniah Janah Sayekti; Muhammad Taufiq Qurrohman; Annisa Banowati (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Dengue Hemorrhagic Fever (DHF) is a life-threatening disease caused by the dengue virus, which consists of four serotypes: DEN-1, DEN-2, DEN-3, and DEN-4. Laboratory examinations supporting DHF diagnosis include complete blood count, urine analysis, serological tests, and viral identification using Reverse Transcriptase Polymerase Chain Reaction (RT-PCR). Prevention efforts focus on eliminating Aedes aegypti mosquito larvae through the implementation of 3M Plus, as well as using mosquito bite prevention products such as aromatherapy candles that are simple and practical for community use. Mancasan Baki Village, Sukoharjo, has experienced a high incidence of dengue cases, including fatalities, highlighting the need for community education on the genetic characteristics and molecular diagnostics of the dengue virus and preventive measures using innovative products. Educational activities were conducted through community presentations and demonstrations on making aromatherapy candles. The effectiveness of the program was measured by comparing participants’ knowledge before and after the intervention. The average pretest score was 6.63, which increased to 8.89 in the posttest. Statistical analysis using a t-test showed a significant difference (p < 0.05). Participant satisfaction results indicated that 64.5% rated the program as good, 32.5% as very good, and 3% as fairly good.